RRBP1 depletion of bone metastatic cancer cells contributes to enhanced expression of the osteoblastic phenotype - Chen, Rui; Wang, Yue; Xu, Yang; He, Yaohui; Li, Qing; Xia, Chun; Zhang, Bing (Frontiers in Oncology, 2022)
Bone metastatic cancer-secreted extracellular factors are capable of modifying the bone microenvironment through interacting with bone cells, including osteoblasts. Reticulum ribosome-binding protein 1 (RRBP1) is substantially expressed in certain bone metastatic cancer cells. This study was undertaken to determine whether RRBP1 from bone metastatic cancer cells affects the osteoblastic phenotype expression. Breast and prostate cancer cells, MDA-MB-231 and PC3, were cultured, respectively, followed by collecting conditioned mediums (CMs) and identifying the abundance of RRBP1 in CMs using LC-MS/MS. MC3T3-E1 cells were cultured with a mixed medium (including CMs from shRRBP1-transduced two-type cancer cells) with or without endoplasmic reticulum (ER) stress inhibitor 4-PBA, followed by measuring the levels of osteoblastic phenotype expression and biomarkers of ER stress using western blotting, qPCR, and ARS staining, respectively. Similar experiments were performed in shRrbp1-transduced MC3T3-E1 cells cultured with a mixed medium (including CMs from the two-type cancer cells). Bone formation parameters were measured in the tibia of nude mice injected with shRRBP1-transduced two-type cancer cells using micro-CT analysis. These results showed that RRBP1 is the sole shared high-abundance protein in CMs from the two-type cancer cells, involving osteoblast differentiation. CMs from shRRBP1-transduced two-type cells boosted the osteoblastic phenotype expression partially through increasing ER stress. CMs from the two-type cancer cells partially offset the similar alterations induced by shRrbp1 in MC3T3-E1 cells. Injection with shRRBP1-transduced two-type cells ameliorated the bone lesions in nude mice. Therefore, RRBP1 depletion of bone metastatic cancer enhanced the osteoblastic phenotype expression, suggesting a role of RRBP1 in the bone microenvironment.